Optimization of production of phycobiliproteins from Spirulina maxima and Spirulina platensis under laboratory conditions - Singh, Surendra; Marskolay, Sonil (International Journal of Psychosocial Rehabilitation, 2020)
Cyanobacteria, especially Spirulina sp., are considered as valuable tool for obtaining phycobiliproteins, which has numerous applications. The present study was conducted to optimize the production of phycobiliproteins from two strains of Spirulina, i.e. S. maxima and S. platensis, grown in CFTRI medium. The optimization was done by changing the light colour, nitrate source and pH of the medium. The results showed that monochromatic light, in red zone, nitrate source and sodium and potassium nitrate as well as pH 10.0 enhanced the production of three major components of phycobiliproteins, phycocyanin (PC), phycoerythrin (PE) and allophycocyanin (APC), as well as chlorophyll a concentration and total cellular proteins, after 30 days of growth. Further, S. platensis proved to be better strain as compared to S. maxima for production of phycobiliproteins in CFTRI medium.